Influence of Decorative Drawing Skills on the Learning Outcomes of Batik Phase F Students of Creative Batik and Textile Craft at SMK Negeri 1 Jabon - Sabrina, Silmy Nurin; Nahari, Inty; Rahayu, Imami Arum Tri; Kharnolis, Mein (PT. Riset Press International, 2025)
The purpose of this research is to find out: 1) To find out how the decorative skills of phase E KKBT students at SMK Negeri 1 Jabon, 2) To determine the learning outcomes of batik craft students in phase F KKBT SMK Negeri 1 Jabon, 3) To determine the effect of students’ decorative drawing skill on improving student learning outcomes in drawing batik craft in phase F KKBT students of SMK Negeri 1 Jabon. This research uses quantitative methods with a sample of 33 students. The instrument in this study was a student batik performance test assessment sheet. The data collection technique was a performance test assessment with simple regression analysis. The results of the study stated: 1) The level of completeness of the decorative variety shows that there are 11 (33%) students who are not complete, and there are 22 (67%) students who are complete. 2) The level of batik completeness shows that 6 (18.18%) students are not complete, and there are 27 (81.81%) students who are complete. 3) There is an effect of knowledge of decorative varieties on batik learning outcomes with the demonstration of variations from the batik learning outcomes variable (Y) caused by skill of decorative varieties (X) of 91.8%.